Why do German companies invest in apprenticeships? : the "Dual System" revisited - Schaack, Klaus [Verfasser] (Klaus Schwarz, 2008)
"The “Dual System” Revisited - The paper offers historical and political explanations, a criticism of neoclassical and "common sense" models in comparative vocational education research, and an inspection of structures, institutions and "boosters" of the "dual system’s" performance. The question, why German companies and private sector institutions "participate" not only in training but also in training design, targets a very clear behavioural difference between German entrepreneurs and the entrepreneurs of many other countries. It is largely a question concerning the social forces which have a decisive say in design, supervision and implementation of training. Klaus Schaack, economist, born 1947, has been working in the field of technical and vocational education and training (TVET) and international TVET cooperation for several German and foreign organizations since 1980. For ten years he has been TVET adviser to the Laotian Ministry of Education, to the South Korean Ministry of Labour and several Korean training agencies including the HRD Service of Korea, the Korea Foundation of Polytechnic Colleges (KOPO) and the Korea Chamber of Commerce and Industry (KCCI). forces which have a decisive say in design, supervision and implementation of training." (Verlag, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; S 4.1.2 Einzelbetriebliche Finanzierung; Duales System; Beruflichkeit; Betriebliche Berufsausbildung; Bildungsfinanzierung; Ausbildungsinvestition; Korporatismus; Sozialpartnerschaft